Wątki ekologiczne zwerbalizowane w albumie przyrodniczym Niny Grzelak "Poznajemy las" - Węgorowska , Katarzyna (Colloquia Litteraria, 2024)
Ecology, as it is broadly understood, is an integral part of the contemporary life of humankind. Numerous ecology principles stated in various publishing proposals remind us of a human’s duties to the environment around them (including the forest). Acccordingly, the purpose of this article is to discuss selected ecological themes presented in Nina Grzelak’s naturalist album „Poznajemy Las”. The subject of linguocultural considerations, on the other hand, is the verbal content: verbal texts and/or verbal comments complementing the beautiful and carefully selected visual texts; photographs and drawings, which together fit not only into the nowadays fashionable ecological discourse, but also contemporary didactics and, above all, education. A thorough reading of the excerpted ecological and biological proposal makes the following clearer to understand: the peculiarities of the forest ecosystem; the habitat of the dead forest trees; the acoustic qualities of the forest, and it reminds us, among other things, of the pragmatic use of the forest tree, and pro-ecological human activities in the forest in winter. All this „linguistic and visual data” make Nina Grzelak’s proposal an unforgettable ecolecture, which while arousing people’s curiosity, and it has an eco-educational purpose.